First Description of the Larva of Nilotonia (Dartia) vietsi (Acari, Hydrachnidia, Anisitsiellidae) - Esen, Yunus; Buğa, Evren; Doğan, Sibel; Doğan, Salih; Erman, Orhan (Fırat University, 2018)
In this study, first description of the larva of Nilotonia (Dartia) vietsi Bader & Sepasgozarian, 1980 was given which is known only from Iran and Turkey. So far, in this genus only the description of larva of Nilotonia (Dartiella) longipora (Walter, 1925) has been given. The similarity and differences between larvae of these two species were evaluated.

Bu çalışmada sadece İran ve Türkiye’den bilinen Nilotonia (Dartia) vietsi Bader & Sepasgozarian, 1980’in larvasının tanımı ilk defa verilmiştir. Nilotonia cinsine ait türlerden şimdiye kadar sadece Nilotonia (Dartiella) longipora (Walter, 1925)’nın larvasının tanımı verilmiştir. Bu çalışmada, bu iki türün larvalarının benzerlik ve farklılıkları değerlendirilmiştir.
Nilotonia (Dartia) vietsi’nin (Acari, Hydrachnidia, Anisitsiellidae) Larvasının İlk Defa Tanımı